CONSUMER TRUST AND ATTITUDES TOWARD NIVEA TELEVISION ADVERTISEMENTS: THE ROLE OF PERCEIVED CREDIBILITY, APPEAL, AND PURCHASING BEHAVIOR (UNIZIK Journal of Marketing, 2025)
This study investigates consumer attitude and trust toward NIVEA’s television advertisement campaigns, focusing on how emotional appeal, message clarity, and perceived authenticity influence brand perception and purchasing behavior. Despite NIVEA’s global brand recognition, uncertainties persist regarding the effectiveness of its TV campaigns in fostering consumer trust and driving purchase intent. The research explores Consumer Attitudes and Trust toward Television Advertisement Campaigns, testing hypotheses through a quantitative approach. Data were collected from 900 respondents via an online survey, examining demographic factors, trust levels, and advertisement perceptions. Statistical methods such as correlation, regression, and descriptive analysis were applied to identify relationships between variables and to predict and explain how independent variables affect the dependent variable. The findings reveal minimal associations between demographic characteristics and consumer responses, with most correlation coefficients near zero and p-values exceeding 0.05 for key variables like age (p = 0.113), gender (p = 0.551), and trust in ads (p = 0.217). An adjusted R-squared value of 0.039 indicates that only 3.9% of the variance in consumer trust can be attributed to perceived ad credibility. The results suggest that demographic targeting alone is insufficient for shaping consumer attitudes toward NIVEA’s TV campaigns. Instead, enhancing ad content through emotional appeal, trust-building narratives, and authentic storytelling is crucial. The study highlights the importance of broader advertising strategies aimed at fostering trust and boosting consumer engagement beyond demographic considerations.
Keywords: Consumer, Attitudes, Trust, Television Advertisement, Nivea Campaigns.